Seismic Vulnerability Assessment of Historical Masonry Aggregate Buildings. The Case of Fes Medina in Morocco. Issue 6 (3rd June 2022) - Stefanini, S.; Rovero, L.; Tonietti, U.
ABSTRACT: Historic urban centers characterised by traditional masonry aggregate patio houses have been studied under many aspects: the patio construction type allows to obtain thermal conditions suitable for particular climatic conditions and introverted interior spaces suitable for specific cultures. Conversely, the seismic vulnerability assessment is not yet thoroughly investigated. This paper proposes a methodology for the seismic vulnerability assessment at the urban scale for traditional masonry aggregate patio houses, developing on Vulnerability Index approach combined with the macroseismic method through vulnerability functions. In particular, an appropriate survey form is proposed by a thorough calibration on the remarkable case study of the Fes medina, UNESCO World Heritage site, which has suffered severe damages from earthquakes occurred in ancient time. The study allowed to realise vulnerability and fragility curves, damage scenarios, and loss scenarios. The method was applied a second time to the case study after simulated structural retrofitting interventions. The vulnerability assessment results are also presented through maps with the Geographic Information System (GIS).